Left ventricular remodeling after transcatheter mitral valve replacement with Tendyne. (25th November 2020) - Fukui, M; Sorajja, P; Goessl, M; Bae, R; Sun, B; Duncan, A; Muller, D; Cavalcante, J
Abstract: Background: Data on changes in left atrial (LA) and left ventricular (LV) volumes after transcatheter mitral valve replacement (TMVR) are limited. Purpose: This study sought to describe the anatomical and functional changes in left-sided cardiac chambers by computed tomography angiography (CTA) from baseline to 1-month after TMVR with Tendyne prosthesis. Methods: We analyzed patients who underwent TMVR with Tendyne prosthesis (Abbott Structural, Menlo Park, CA) between 2015 and 2018. Changes in LV end-diastolic volume (LVEDV), ejection fraction (LVEF), mass (LV mass), LA volume and global longitudinal strain (GLS) were assessed at baseline and at 1-month after TMVR with CTA. Specific Tendyne implant characteristics were identified and correlated with remodeling changes. Results: A total of 36 patients (mean age 73±8 years, 78% men, 86% secondary MR) were studied. There were significant decreases in LVEDV (268±68 vs. 240±66ml, p<0.001), LVEF (38±10 vs. 32±11%, p<0.001), LV mass (126±37 vs. 117±32g, p<0.001), LA volume (181±74 vs. 174±70 ml, p=0.027) and GLS (−12.6±5.1 vs. −9.5±4.0%, p<0.001) from baseline to 1-month follow-up. Favorable LVEDV reverse-remodeling occurred in the majority (30 of 36 patients, or 83%). Closer proximity of the Tendyne apical pad to the true apex was predictive of favorable remodeling (pad distance: 25.0±7.7 vs. 33.5±8.8mm, p=0.02 for those with and without favorable remodeling). Conclusions: TMVR with Tendyne results in favorable left-sided chamber remodeling in the majority of patients treated, as detected on CTA at 1-month after implantation. CTA identifies the favorable post-TMVR changes, which could be related to specific characteristics of the device implantation. Funding Acknowledgement: Type of funding source: None